Ground based follow-up for Gaia Science Alerts: First results. Issue 67 (17th July 2015) - Fraser, M.; Altavilla, G.; Blagorodnova, N.; Campbell, H.C.; Clementini, G.; Miguel, E. de; Gilmore, G.; Hodgkin, S.T.; Jonker, P.G.; Koposov, S.; Rixon, G.; Rybicki, K.; et al.
Abstract : The Gaia Science Alerts project (GSA) aims to augment a precision survey of the Milky Way with a controlled, precision survey of all classes of transient phenomena. While onboard BP/RP spectra from Gaia will ultimately allow us to classify many Gaia Alerts based on Gaia data alone, in the initial phases of the GSA project it is necessary to verify and classify discoveries with ground-based spectroscopic followup. In this article, we describe a subset of the ongoing Gaia Alerts followup programmes, and some of the initial science results from this work.